Implementasi Pengarusutamaan Gender Pada Objek Wisata Banyuwana Waterfall - Ni Made Rosita Dewi; Karimah Liana; Ni Putu Wiwin Listya Adnyani; I Gusti Ngurah Desta Permana Putra; I Putu Adi Permana Putra (Aplikasi Administrasi: Media Analisa Masalah Administrasi, 2024)
The management of the Banyuwana Waterfall tourist attraction based on community-based tourism (CBT) has contributed to the local community's income. The massive growth of tourism provides opportunities for men and women to participate in it. This is related to the context of gender equality. Gender issues must be integrated into sustainable development in various sectors, including tourism. This study raises the topic of gender mainstreaming at the Banyuwana Waterfall tourist attraction to assess the performance of policies and gender equality in tourism management. This study aims to understand and analyze the implementation of gender mainstreaming policies at the tourist attraction. The research method used is a qualitative descriptive approach, with data collection techniques through non-participatory observation, in-depth interviews, and documentation studies. Data analysis is carried out through interactive qualitative data analysis techniques through data collection, data reduction, data presentation, and conclusion. Data validity testing is carried out through data triangulation. The study results indicate that implementing gender mainstreaming at the Banyuwana Waterfall tourist attraction positively contributes to the sustainability of fair and inclusive tourism. However, various challenges exist, especially regarding the implementer's understanding of policy standards and targets. Economic, social, and political factors also influence the implementation of PUG policies, but gender dominance and bias in tourism development are still significant obstacles. To overcome this, educational efforts, cross-sector collaboration, and integration of gender-responsive policies in tourism development planning are needed to optimize the implementation of gender mainstreaming to achieve sustainable development goals.